Assessing the Effect of Budget Efficiency on Educational Staff Performance in Public Universities of West Aceh Regency - Zarita, Santi Septiana; Agustian, Kusmira; Muhammad; Novriza, Ferdiansyah; Saputra, Herdian (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
Budget efficiency represents a critical determinant of organizational performance in resource-constrained higher education environments, yet empirical evidence examining its specific impact on non-academic support staff remains limited, particularly in regional Indonesian universities. This study investigates the relationship between budget efficiency and educational support staff performance in public universities of West Aceh Regency, guided by Performance-Based Budgeting theory and Goal-Setting Theory. Employing a sequential explanatory mixed-methods design, the study collected quantitative data from 80 educational support staff through validated questionnaires (Cronbach's α = 0.89-0.91) and qualitative insights from 10 key informants via semi-structured interviews. Pearson correlation and hierarchical multiple regression analyses examined relationships between budget efficiency dimensions (allocation accuracy, utilization effectiveness, transparency) and performance outcomes (task efficiency, service quality, professional development). Budget efficiency demonstrated strong positive correlation with staff performance (r = 0.674, p < 0.001) and accounted for 45.4% of performance variance (R² = 0.454, F (1,78) = 64.73, p < 0.001). Allocation accuracy emerged as the dominant influence factor (score: 88/100), followed by transparency/accountability (85/100) and staff participation (82/100). Qualitative findings revealed dual pathways: material mechanisms (resource adequacy enabling task execution) and psychological mechanisms (perceived organizational support enhancing motivation). Budget efficiency influences educational support staff performance through interconnected material and motivational pathways rather than resource availability alone. Universities should prioritize participatory budgeting, transparent financial reporting, and allocation-need alignment. Policymakers must recognize that performance-based funding requires parallel institutional capacity development to ensure equitable efficiency gains across administrative units.